2015
DOI: 10.1080/03036758.2015.1051549
|View full text |Cite
|
Sign up to set email alerts
|

The use and value of citizen science data in New Zealand

Abstract: There has been significant growth worldwide of citizen science projects involving community members collecting environmental data. The following study is based on questionnaire responses from 296 community environmental groups and interviews with 34 project partners (e.g. resource managers and scientists) and examines the use and value of citizen science data in New Zealand. Frequency counts and inductive thematic analysis were used to examine the quantitative and qualitative data, respectively. Groups reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 21 publications
1
35
0
Order By: Relevance
“…The past 20 years have seen a global increase in citizen science projects and interest in their facilitation (Bonney et al 2014;Peters et al 2015). The definition of citizen science used here aligns with Roy et al's (2012) description of "involvement of volunteers in science" (p. 5).…”
Section: Introductionmentioning
confidence: 74%
“…The past 20 years have seen a global increase in citizen science projects and interest in their facilitation (Bonney et al 2014;Peters et al 2015). The definition of citizen science used here aligns with Roy et al's (2012) description of "involvement of volunteers in science" (p. 5).…”
Section: Introductionmentioning
confidence: 74%
“…This lack of integration is due to several factors, in particular, doubts about the reliability of volunteer-collected data , Hunsberger 2004, Gollan et al 2012, Bonney et al 2014. In New Zealand, such doubts among decision makers result in a lack of council support to maximize data quality and lend credibility to community monitoring, while doubts among volunteers reduce their motivation to continue collecting data (Peters et al 2015b). Providing evidence that community-based monitoring data can be reliable, therefore, would address a critical barrier to successful integration of community-based monitoring in decision making.…”
Section: Introductionmentioning
confidence: 99%
“…Most have concluded that, with appropriate resourcing and robust protocols, volunteer data agree closely enough with professional data for use in government http://www.ecologyandsociety.org/vol21/iss4/art32/ Involving community members in monitoring increases not only their ability to contribute data, but also their ability to discuss their knowledge with experts (described as "interactional expertise" by Carolan 2006). Community members participating in environmental monitoring also commonly show increased scientific literacy, greater awareness of local ecosystems and wider environmental issues, stronger social networks including relationships with local government, and greater interest in freshwater planning (Bliss et al 2001, Savan et al 2003, Overdevest et al 2004, Pollock and Whitelaw 2005, Stepenuck and Green 2015, Peters et al 2015b. All of these benefits may lead to more effective community engagement with government in freshwater decision making.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although groups' data are primarily used in situ, e.g. for managing their own projects (Peters et al 2015a), providing more cohesive evidence that outcomes from CBEM activities across community groups demonstrate improvements in biodiversity may strengthen the case for more secure, longer-term funding.…”
Section: Monitoring Challengesmentioning
confidence: 99%